Expulsion Rate of Post Placental Intrauterine Device Placed in Women Delivered by Caesarean Section and Vaginal Delivery - FARIHA SHOUKAT, SADIA NAZIR, KIREN KHURSHID (Journal of Fatima Jinnah Medical University, 2018)
Background: Pakistan has become the fifth most populous nation of the world. Use of post placental intrauterine device may be helpful in countries like Pakistan where women have limited access to medical care and family planning services. The aim of this study was to determine the expulsion rate of post-placental intrauterine device (IUCD) placed in women delivered by caesarean section or vaginal delivery. Patients and Methods: This descriptive case series study was carried out in the Department of Obstetrics & Gynecology Sir Ganga Ram Hospital, Lahore from August 2014 to August 2015. All women delivering vaginally or by Caesarean section who opted for intrauterine contraceptive device after counseling were enrolled in the study. The expulsion rate was noted at 6 weeks and 6 months follow up visit or earlier if expelled. Data was collected on pretested Performa. Results: In this study, out of 160 cases, 40.63% (n=65) were between 18-30 years of age while 59.37% (n=95) were between 31-50 years of age having mean age of 32.2 years. Among them 27.5% (n=44) had 1-3 para and 72.5% (n=116) had >3 para. Frequency of expulsion of post placental IUCD was recorded as 13.13% (n=21). No significant association was found for age, parity and mode of delivery. Conclusion: The frequency of expulsion rate of post placental intrauterine contraceptive device inserted in women delivered by cesarean section and vaginal delivery is low. Therefore, this method can be opted for effective family planning in Pakistani population.